A preliminary study of trust in internet-based inter-organisational systems. (23rd September 2008) - Tong, V.W.L.; Lai, I.K.W.
Internet-based inter-organisational systems (IIOS) help to strengthen supply chain collaboration so as to gain greater competitive advantages. However, IIOS are not popular in applications. The problems of trust in IIOS perceived by the users pose the hesitation to adopt IIOS. Thus there is a need to have a model to examine the influence of the trust factors on the supply chain members towards the IIOS adoption. In this study, a holistic trust model is employed and a preliminary survey is conducted to evaluate the importance of the trust factors on the adoption of IIOS. This study provides a theoretical model and methodology that can be used for future research on the success of IIOS adoption.